Economic Business Analysis of Polyculture Pond Cultivation of Shrimp and Milkfish in Turikale District, Maros Regency - Alfian Adisaputra Hy; Aris Baso; Sutinah Made; Sitti Fakhriyyah (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2026)
Aquaculture plays a strategic role in supporting food security, economic growth, and the welfare of coastal communities in Indonesia. Turikale District in Maros Regency is one of the regions with high potential for implementing polyculture pond systems, particularly for black tiger shrimp Penaeus monodon and milkfish Chanos chanos. This study aimed to evaluate the economic aspects of polyculture pond farming in this area, focusing on profitability and economic feasibility. The research was conducted in response to the growing demand for efficient and sustainable aquaculture models to optimize fisheries resource management. The study employed a descriptive quantitative approach, collecting primary data through interviews, questionnaires, and direct field observations involving 24 fish farmers in Taroada Village. Data analysis included calculations of total production costs, total revenues, profit margins, and R/C ratio analysis to assess business efficiency. The total production cost per cycle (6 months) was Rp18,242,320.61, comprising fixed costs of Rp1,036,877.86 and variable costs of Rp17,205,442.75. The total revenue reached Rp27,857,697.22, yielding a net profit of Rp9,615,376.598. Feasibility analysis revealed an R/C ratio of 1.53, indicating that for every Rp1 spent, the business generated Rp1.53 in revenue, thus confirming its economic viability. These findings demonstrate that polyculture farming of black tiger shrimp and milkfish not only provides significant financial returns to farmers but also has the potential to enhance local economic development. It is recommended to expand the implementation of this system while ensuring operational efficiency and sustainable pond management practices.